Time to abandon microalbuminuria? - Ruggenenti, P.; Remuzzi, G. (Kidney international, 2006)
The term microalbuminuria – a urinary albumin excretion (UAE) between 20 and 200μg/min – has been introduced to identify subjects at increased risk of renal and cardiovascular disease. However, the relationship between albuminuria and risk is not restricted to the microalbuminuric range and extends to as low as 2–5μg/min. On the contrary, the increase of UAE above 200μg/min (macroalbuminuria) heralds the onset of proteinuria (urinary protein excretion above 0.5g/24h) and progressive renal and cardiovascular disease. Albuminuria is a component of the metabolic syndrome and may represent a marker of the increased risk of renal and cardiovascular disease associated with insulin resistance and endothelial dysfunction. Proteinuria is a sign of established kidney damage and plays a direct pathogenic role in the progression of renal and cardiovascular disease. Albuminuria reflects functional and potentially reversible abnormalities initiated by glomerular hyperfiltration, proteinuria, a size-selective dysfunction of the glomerular barrier normally associated with glomerular filtration rate (GFR) decline that may result in end-stage renal disease. Thus, the limit of 200μg/min segregates patients with albuminuria or proteinuria who are at quite different risk. Among subjects with albuminuria, however, there is a continuous relationship between albumin excretion and risk and no lower bound between normal albuminuria and microalbuminuria can be identified that segregates subjects at different risk. Thus, the terms microalbuminuria and macroalbuminuria could be replaced by the concepts of albuminuria- and proteinuria-associated diseases. Future studies are needed to identify levels of albuminuria below which therapy is no longer beneficial.